Effect of Competence And Work Motivation on Employee Performance PT. Rotella Mandiri Persada Perbaungan - Ajeng Retningjati; Lydia Yunita; Martua sitorus (Institute of Computer Science (IOCS), 2018)
This study aims to Determine the effect of work competence and motivation on employee performance at PT. Rotella Perbaungan Mandiri Persada. The research method used in this study is a quantitative method. Quantitative Methods is a research method that aims to describe what happens to the object with an effort to describe, record, analyze and interpret existing data. The population in this study were all employees of PT. Rotella Perbaungan Persada Mandiri totaling 55 people, while the sample is the entire population. Sampling uses a saturated / roomates census sampling technique uses the entire group of research of data in the population as research elements and subjects. The statistical test used is using the classic assumption test, hypothesis testing, multiple linear analysis, correlation coefficient and determinant coefficient. The results of this study indicate that partially a significant influence on competence on the performance of employees of PT Persada Mandiri .otella Perbaungan of tcount7,921> TTable 1,674. Partially significant influence between work motivation on employee performance thitung2,329> t table1,674. The significant effect between competency and work motivation on employee performance simultaneously is the value of Fcount 31.625> Ftable 3.18. And R-square of 0.549% and 45.1% is influenced by other factors.